The Fungicidal action of Some Natural Products (Denture cleansers ) on Acrylic Denture Base Material - Nadira A. Hatim; Rana Rabee AL-Sumaidae (University of Mosul, College of Dentistry, 2011)
Aim: To evaluate some natural products (soda+ vinegar, soda + thymol , saturated salt solution) compared with the commercial denture cleanser (Protifex), for disinfection of acrylic denture base material from C. albicans (in vitro ). Materials And Methods: Thirty five samples, (10 x 10 x 2 mm length, width, and thickness respectively), were prepared from heat cured acrylic resin denture base material (Major heat cured acrylic resin ), using MacFarland Standard Bacteriologica Solution technique, tube No.2., using a light microscope with camera connected to computer for testing anti fungal efficiency of these natural denture cleansers (soda, vinegar, thymol, saturated salt solution). This procedure was done after 1 hour, 4 hours, and 8 hours of immersion. in comparison with samples immersed in distilled water, (Control). Results: The results demonstrated that at P=0.05 there were significant differences between all prepared solutions and control. The best prepared natural solution was saturated salt solution. There were significant differences between all times of immersion, the best was 8 hrs. Conclusions: All the prepared natural denture cleansers were considered as fungicidal disinfectants, and a proper disinfection of the acrylic denture base material requires 8 hrs of immersion in the prepared disinfectant solutions. The best prepared natural solution was saturated salt solution.